Challenges of Integrating Transferable Skills in Business Education Programme in Nigerian Colleges of Education - Obi B. Irukaku , (SR. Mary Noeleen); C. Ile , Madu; Chibuzo , Nkiruka F. (African Journal of Education,Science and Technology (AJEST), 2025)
Challenges of integrating transferable skills into the business education programme in Nigerian colleges of education necessitated the study. Two research questions and two hypotheses tested at 0.05 level of significance guided the study. The study employed survey research design and the population was 71 business educators from two public colleges of education in Anambra State. Questionnaire was used for data collection. Mean and standard deviation were used to analyze the research question while t-test was used to test the hypotheses. The findings of this study revealed that communication skills, information technology skills, research skills and professionalism and work ethics were identified as key transferable skills that should be integrated in business education. The study further identified lack of adequate lecturers with the required competencies; deteriorating infrastructure; inadequate ICT facilities for simulations and poor funding of business education programme as some of the challenges of integrating transferable skills into business education programme. The test of hypotheses indicated generally that there was no significant difference in the opinions of experienced and less experienced business educators on transferable skills that should be integrated in business education as well as the challenges of integrating these skills in business education in Nigerian colleges of education. It was recommended, among others, that proper workshop on how to integrate transferable skills should be organized for business educators in order to enable them have in-depth knowledge and high level of competence in this area and also that business educators should adopt teaching methods that are activity based in order to enhance the development of transferable skills in the students.